The association between trauma and melanoma in the Chinese population: a retrospective study. (7th March 2013) - Zhang, N.; Wang, L.; Zhu, G.N.; Sun, D.J.; He, H.; Luan, Q.; Liu, L.; Hao, F.; Li, C.Y.; Gao, T.W.
Abstract Background The association between trauma and melanoma has been a controversial issue. Objectives To analyse the profiles of melanoma, and to determine whether trauma is associated with development of acral melanoma in the Chinese population. Patients and Methods Retrospective analysis of 685 cases of cutaneous melanoma in the dermatology departments of Xijing Hospital in northwestern China and Xinan Hospital in southwestern China from 1982 to 2011. Results Of the 685 patients included in the study, 437 (63.8%) suffered from melanoma on the extremities. A total of 104 patients (15.2%) exhibited an association between trauma and melanoma. The primary anatomic sites of the tumours were the upper extremities (17, 16.3%), lower extremities (74, 71.2%) and other sites (13, 12.5%). Among these cases, the extremities were with remarkably higher risks of post‐trauma melanoma than the other sites [adjusted odds ratio (OR) 3.968; 95% confidence interval (CI) 2.267–5.592]. Notably, patients in the south part of China were with a stronger risk of post‐trauma melanoma on the lower extremities than those in the north (adjusted OR 1.764; 95% CI 1.192–2.666) part. In addition, a significant higher risk of post‐trauma melanoma on the extremities was observed in the male gender (adjusted OR 1.848; 95% CI 1.186–2.887). Conclusions Our findings provide epidemiological evidence for a potential association between traumatic events and melanoma of the extremities, especially the lower limbs, where a history of trauma is more likely.